A Comparative Parametric Analysis of the Ground Fault Current Distribution on Overhead Transmission Lines - VINTAN, M. (Advances in Electrical and Computer Engineering, 2016)
The ground fault current distribution in an effectively grounded power network is affected by various factors, such as: tower footing impedances, spans lengths, configuration and parameters of overhead ground wires and power conductors, soil resistivity etc. In this paper, we comparatively analyze, using different models, the ground fault current distribution in a single circuit transmission line with one ground wire. A parametric comparative analysis was done in order to study the effects of the non-uniformity of the towers footing impedances, number of power lines spans, soil resistivity, grounding systems resistances of the terminal substations etc., on the ground fault current distribution. There are presented some useful qualitative and quantitative results obtained through a complex dedicated developed MATLAB 7.0 program.